Civilization and Globalization in a World of Turmoil - Mehdi Mozaffari (Glocalism: Journal of Culture, Politics and Innovation, 2019)
The pivotal question concerns the compatibility or non-compatibility of the current unprecedented global system with a world made up of a plurality of civilizations. In other words, can the world become vastly globalized without this having any substantial impact on civilizations? What consequences will the speedy globalization have on the identity and dignity of various human entities; both as individuals and as a collectivity? The interplay between “globalization” and “civilization” as well as the interaction between globalization and local identity are the main issues of the present study.